Renovation of the Urban Environment - Historical Precedents (Czech Journal of Multidisciplinary Innovations, 2022)
The article deals with the problems of preserving the environment of architectural monuments and historical parts of the city of Samarkand. The problems of modern construction in protected and buffer territories are also consecrated. Examples of the negative consequences of the demolition and restructuring of historically formed civil buildings and structures are given. This leads to the destruction of background buildings and reduces the level of perception and uniqueness of historical architectural monuments